2021
DOI: 10.1186/s40981-021-00423-1
|View full text |Cite
|
Sign up to set email alerts
|

Continuous pericapsular nerve group block for postoperative pain management in total hip arthroplasty: report of two cases

Abstract: Background Total hip arthroplasty (THA) is one of the surgical procedures associated with severe postoperative pain. Appropriate postoperative pain management is effective for promoting early ambulation and reducing the length of hospital stay. Effects of conventional pain management strategies, such as femoral nerve block and fascia iliaca block, are inadequate in some cases. Case presentation THA was planned for 2 patients with osteoarthritis. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Hip arthroplasty is associated with high degree postoperative pain. Effective postoperative pain management leads to early recovery and reduces hospital stay (21,22). In our study, it was found that there was a negative correlation between the vitamin D values of our patients and the postoperative VAS scores at the 1st, 2nd, 6th, 8th, and 24th hours, and the VAS score increased as the vitamin D level decreased.…”
Section: Vitamin D Level and Acute Postoperative Painsupporting
confidence: 51%
“…Hip arthroplasty is associated with high degree postoperative pain. Effective postoperative pain management leads to early recovery and reduces hospital stay (21,22). In our study, it was found that there was a negative correlation between the vitamin D values of our patients and the postoperative VAS scores at the 1st, 2nd, 6th, 8th, and 24th hours, and the VAS score increased as the vitamin D level decreased.…”
Section: Vitamin D Level and Acute Postoperative Painsupporting
confidence: 51%
“…Among clinical studies utilizing PENG block ( n = 29), most are low-quality case reports/series [ 1 , 2 , 3 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ], but one cohort study [ 59 ] and eight randomized controlled trials [ 4 , 5 , 60 , 61 , 62 , 63 , 64 , 65 ] appeared in the literature after late 2020. Definite post-procedural quadriceps weakness after PENG block was reported in two case reports [ 2 , 3 ] and two RCTs [ 4 , 5 ] (group A).…”
Section: Resultsmentioning
confidence: 99%
“…Among PENG block studies that reported no post-procedural quadriceps weakness or made no mention of motor function at all, clinical manifestations of extra-IP spread of local anesthetics either as observed injectate spread to the FIC in ultrasound images [ 42 ], sensory loss of dermatomes corresponding to the femoral nerve [ 43 , 44 , 45 , 46 , 47 , 49 , 50 , 51 ], or an absence of statistically significant difference in quadriceps strength in patients receiving a supra-inguinal fascia iliaca compartment block (SI-FICB) [ 60 , 61 ] were found in nine case reports/series [ 42 , 43 , 44 , 45 , 46 , 47 , 49 , 50 , 51 ] and two RCTs [ 60 , 61 ] (group B). Nine case reports/series [ 1 , 48 , 52 , 54 , 55 , 56 , 57 , 64 , 66 ], one cohort study [ 60 ], and four RCTs [ 62 , 63 , 64 , 65 ] using PENG block specifically reported no motor block at all (group C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation